Polski przedsiębiorca a europejskie prawo konsumenckie - wybrane zagadnienia dotyczące ochrony przed nieuczciwą reklamą - Popek, Małgorzata (Polish Entrepreneur Vs. the European Consumer Law, Selected Issues Concerning the Protection Against Dishonest Advertising, 2006)
The problems regarding protection of the widely defined consumer as the weaker participant of the market game have been discussed in the article. In the light of the European law an attempt has been made to define the consumer and the extent of his protection. The article also analyses the European Union regulations concerning consumer protection against dishonest advertising (misleading and comparative advertisements) and the problem of taking responsibility for dishonest advertising.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1116, s. 332-339